2020
DOI: 10.2196/19777
|View full text |Cite
|
Sign up to set email alerts
|

Online Japanese-Language Information on Lifestyle Factors Associated With Reduced Fertility: Content Analysis

Abstract: Background Approximately one-third of Japanese couples currently worry or previously worried about infertility. To develop strategies for the primary prevention of infertility as a population approach, it is important for the general population to be knowledgeable about fertility and infertility. The internet may contribute to the dissemination of information regarding infertility and fertility. However, few studies have examined online information about fertility. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Although nutritional factors such as healthy dietary patterns are evidence-based lifestyle factors associated with fertility [13,39], they are covered in the articles to a greater extent than other factors. This is consistent with our findings from a previous study of online content [22]. A 2016 survey conducted in Japan reported that 59.7% of female respondents and 32.0% of male respondents reconsidered their dietary habits when pregnant or trying to conceive [15] consistent with the emphasis on nutrition we observed in the magazine articles.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although nutritional factors such as healthy dietary patterns are evidence-based lifestyle factors associated with fertility [13,39], they are covered in the articles to a greater extent than other factors. This is consistent with our findings from a previous study of online content [22]. A 2016 survey conducted in Japan reported that 59.7% of female respondents and 32.0% of male respondents reconsidered their dietary habits when pregnant or trying to conceive [15] consistent with the emphasis on nutrition we observed in the magazine articles.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies on infertility information analyzed online information on lifestyle factors associated with reduced fertility [22], newspaper articles on assisted reproductive technology [23], the readability, suitability, and quality of online information on infertility [24,25], and infertility-related videos [26]. Individuals diagnosed with infertility may obtain accurate information from healthcare providers.…”
Section: Introductionmentioning
confidence: 99%
“…This compartmentalization of female sexuality based on age and maternal status provides a small window of time for young women to get married and involve themselves in reproductive sex. Married women without children are encouraged to engage in so-called kodukuri, literally trying to conceive a child, or more recently, ninkatsu, meaning active engagement in pregnancy (similarly to sh ukatsu, job hunting), within Japan's rapidly aging society (Yokota et al, 2020). In this social context, women in their 30s and 40s with children are in limbo.…”
Section: Women Buying Sexmentioning
confidence: 99%
“…3 The World Health Organization (WHO) has classified infertility as a major public health problem worldwide, affecting about 186 million people, including 15% of women of childbearing age. [4][5][6] In recent years, infertility has seriously threatened the progress of human civilization, and the US Centers for Disease Control and Prevention has proposed prioritizing the diagnosis and treatment of infertility. 7 Epidemiological studies have shown that infertility is a fertility disorder caused by a variety of etiologies.…”
Section: Introductionmentioning
confidence: 99%